The determinants of greenhouse gas reduction levels among smallholder farmers: insights from the adoption of climate-smart dairy strategies in Central Kenya - Chelang’a, Naomi Chebiwot; Mathenge, Mary; Otieno, Dickson Okello; Sassi, Maria (Frontiers in Climate, 2025)
In Kenya’s dairy sector, climate change mitigation focuses on sustainable milk production. However, dairy producers often overlook emission reduction, creating a gap between national policies and local practices. This paper aims to identify the factors, including smallholder entrepreneurial orientation, socio-economic characteristics, and institutional influences, that drive the adoption and uptake intensity of on-farm greenhouse gas reduction measures in the dairy sector, particularly among smallholder producers in Nyandarua County, Kenya. The study uses a fractional response model to examine factors influencing greenhouse gas reduction at the farm level based on survey data from 385 dairy farmers. Greenhouse gas reduction was measured using a composite index, with proxies drawn from the literature. Key factors influencing greenhouse gas reduction include education, social capital, entrepreneurial orientation, awareness, and risk perception. The study recommends that the national and county governments promote and support the adoption of climate-smart dairy strategies that increase milk production while simultaneously reducing greenhouse gas emissions. This support could include technical assistance, financial support and educational programs to encourage complementary adoption by dairy farmers.